Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s11886-021-01487-2
|View full text |Cite
|
Sign up to set email alerts
|

Remote monitoring and telemedicine in heart failure: implementation and benefits

Abstract: Purpose of review Remote monitoring (RM) of cardiac implantable electronic devices (CIEDs) is recommended as part of the individualized multidisciplinary follow-up of heart failure (HF) patients. Aim of this article is to critically review recent findings on RM, highlighting potential benefits and barriers to its implementation. Recent findings Device-based RM is useful in the early detection of CIEDs technical issues and cardiac arrhythmias. Moreover, RM allows the continuous monitoring of several patients' c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 107 publications
0
21
0
1
Order By: Relevance
“…Of 45 total programs, cardiology has the highest number of absolute frequency (7) followed by endocrinology (6) and psychology (4). The specialties that have two positive answers are rehabilitation/speech therapy, pneumology, psychiatry, vulnology, nephrology, neurology, pediatrics, and gynecology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 45 total programs, cardiology has the highest number of absolute frequency (7) followed by endocrinology (6) and psychology (4). The specialties that have two positive answers are rehabilitation/speech therapy, pneumology, psychiatry, vulnology, nephrology, neurology, pediatrics, and gynecology.…”
Section: Resultsmentioning
confidence: 99%
“…This result can be explained by the abundant presence of devices to monitor parameters in chronic patients, especially those affected by heart failure and diabetes. For chronic heart failure, the cardiac implantable electronic devices used to treat bradyarrhythmia and tachyarrhythmia nowadays have been implemented with the feature of remote monitoring, to gather, store, and transmit data regarding the patients’ parameters to clinicians [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides simple clinical parameters that allow the identification of patients at higher risk of incident clinical AF and/or long-lasting AHRE episodes which may warrant closer follow-up visits. In consideration of the risk of stroke/thromboembolic events associated with asymptomatic clinical AF, not different from the risk associated with symptomatic clinical AF [17], prompt initiation of anticoagulation is required in patients at risk who develop clinical AF during follow-up, independently on symptoms, and this stresses the value of close monitoring of patients presenting with AHRE, also with the aid, if possible, of remote monitoring [18]. We found that CHA 2 DS 2 -VASc score was independently associated with the composite outcome of clinical AF and longest AHRE episode ≥24 h and also predicted clinical AF per se.…”
Section: Discussionmentioning
confidence: 99%
“…There would also be a rush so that patients could quickly send messages to their families. Imberti et al [13] found that device-based remote monitoring (RM) was useful in the early detection of cardiac implantable electronic devices (CIEDs) technical issues and cardiac arrhythmias. Moreover, RM allowed the continuous monitoring of several patients' clinical parameters associated with impending heart failure (HF) decompensation, but there was still uncertainty regarding its effectiveness in reducing mortality and hospitalizations.…”
Section: Related Workmentioning
confidence: 99%
“…GRU uses the update gate to determine the information read from the memory content and the previous unit. The calculation process is shown in formula (10) to formula (13). The GRU model can use the reset gate to store past information.…”
Section: Grumentioning
confidence: 99%